Performance monitoring of Kuantan-Gambang (FR 2) and Gambang toll plaza (FR 222)-Muadzam (FR 12) cross junction using Malaysian intelligent traffic system (MITS) - Wong Choon Kit, Kevin (2019)
Nowadays, traffic monitoring using Supervisory Control And Data Acquisition (SCADA) system is more efficient and accurate. The objective of this project is to come up as a user manual for the engineers and also the users. There are so many engineers that are still using manual counting and also lack of know how to use SCADA system as a traffic monitoring tools in real life. In this project will show the step by step of collecting the traffic data using the Malaysian Intelligent Traffic System (MITS), it is one of the SCADA system. There are so many different types of data, such as traffic volume, vehicle classification, reporting errors, setting time, traffic queueing, green time, junction time setting and also live view of the junction. MITS could be a great SCADA system for traffic monitoring in Malaysia and also helps the engineers for collecting information and data in the future.